Water sanitation, hygiene and the prevalence of diarrhea in the rural areas of the delta region of Myanmar. (16th December 2021) - Ko, Shane Htet; Sakai, Hiroshi
Abstract: Myanmar is an agriculture-based country with 70% of the total population residing in rural areas. Around half of the total population in Myanmar has to consume water from unimproved sources. The prevalence of diarrhea due to contaminated drinking water is high even in urban areas. The urban community may expect the provision of municipal water supply in the near future if the current revolution against military dictatorship succeeds. However, the rural areas have less or no chance to get quality water because of a lot of other prioritized tasks. Household water treatment is encouraged to be implemented as one of the national water safety plans for rural water supply in Myanmar. This study explored the diarrhea prevention awareness of the rural community using a questionnaire survey. The microbial quality parameters of drinking water sources were also examined. Fecal coliform contamination was detected in all examined drinking water sources. A significant association was found between drinking untreated water and the occurrence of diarrhea. The percentage of people who applied the diarrhea preventive measures was low. Even if they knew how to prevent the disease, very few people applied the measures in reality. Therefore, measures to cause behavioral change should be initiated, together with awareness raising, to promote diarrhea prevention in the community. HIGHLIGHTS: Insight into the public health system in rural Myanmar. Prevalence of diarrhea among the rural community where there is no public water supply. Public awareness on diarrhea prevention and treatment. Tendency to apply mitigation measures. Suggestions to strengthen public health coverage in rural Myanmar.